Gold Coast Criteria in ALS Diagnosis: A Real-World Experience - Lucia Ferullo; Barbara Risi; Filomena Caria; Emanuele Olivieri; Loris Poli; Stefano Gazzina; Ugo Leggio; Enrica Bertella; Giorgia Giovanelli; Beatrice Labella; Alessandro Padovani; Massimiliano Filosto (Brain Sciences)
Background: Revised El Escorial (rEEC) and Awaji criteria are currently used for diagnosing and categorizing amyotrophic lateral sclerosis (ALS). However, they are complex; their sensitivity is still not optimal for research purposes, and they present high inter-rater variability in clinical practice. To address these points, in 2019, a new set of diagnostic criteria was proposed, namely the Gold Coast criteria (GCC), characterized by a dichotomous diagnostic categorization, i.e., ALS or not ALS. Methods: In order to investigate the sensitivity, specificity, and clinical usefulness of GCC in a practical clinical setting, we retrospectively evaluated 131 patients diagnosed with ALS and 104 control subjects. ALSFRS-R score, electrophysiological tests, neuroradiological investigations, and CSF analysis were obtained. rEEC, Awaji, and GCC were applied at the first and last evaluations. Results: The sensitivity of GCC (93.1%; 96.1%) was greater than rEEC (71.8%; 87%) and Awaji criteria (77.8%; 89.3%) both at the first visit and last follow-up. The GCC’s specificity (28.8%) is lower than that of the other two criteria (rEEC 45.2%; Awaji 43.3%). Conclusions: Our study suggests that in a real-world setting, the GCC are more sensitive and have substantially lower risk of false negative diagnoses than rEEC and Awaji criteria. Although rEEC had the highest specificity, they may delay the diagnosis. Systematically using the GCC could help to achieve an earlier diagnosis and quickly refer patients to the correct management. The low specificity of GCC is likely to not significantly impact patient recruitment in clinical trials; therefore, its use might allow a faster and earlier enrollment.